ANALISIS PENERAPAN MANAJEMEN SUMBER DAYA MANUSIA DI UNIVERSITAS PAMULANG (STUDI KASUS DI UNIVERSITAS PAMULANG) - Muhammad Ali (Universitas Pamulang, 2018)
This study aims to analyze the program of improving the quality of human resources, especially lecturers and administrative staff in accordance with Tri Dharma Perguruan Tinggi. This is considering that human resources are a very important factor in moving the wheel of education at Pamulang University. The methodology used in this research is descriptive research method, while the sample in this study are employees of Pamulang University, both supporters and lecturers, amounting to 164 respondents. The method of analysis used in this research is the method of Importance Performance Analysis, with the tools of Cartesius diagram analysis. The results show that at this time Pamulang University has tried to implement human resource management, but in the implementation there are still many management policies that have not been applied. However, in the implementation of the University Pamulang always try as much as possible to perform various actions and activities to make manajemenisasi of existing human resources. Implementation of human resource management must pay attention to environmental aspects and social aspects. organizing, directing, controlling, development, compensation, integration, planning, procurement, maintenance and separation. The pattern of application of human resource management can follow based on the interests and purposes described in Cartesian diagram where the application is adjusted to: 1) First priority: organizing, directing, controlling, development, compensation and integration, 2) Keep It: planning, 3) Leave it: labor supply, maintenance and separation. Key words: Application of Human Resources